An efficient core–shell fluorescent silica nanoprobe for ratiometric fluorescence detection of pH in living cells. Issue 15 (13th June 2016) - Fu, Jingni; Ding, Changqin; Zhu, Anwei; Tian, Yang
Abstract : An efficient core–shell fluorescent silica nanoprobe was developed for ratiometric fluorescence imaging of pH variation in ouabain-treated HeLa cells. Abstract : Intracellular pH plays a vital role in cell biology, including signal transduction, ion transport and homeostasis. Herein, a ratiometric fluorescent silica probe was developed to detect intracellular pH values. The pH sensitive dye fluorescein isothiocyanate isomer I (FITC), emitting green fluorescence, was hybridized with reference dye rhodamine B (RB), emitting red fluorescence, as a dual-emission fluorophore, in which RB was embedded in a silica core of ∼40 nm diameter. Moreover, to prevent fluorescence resonance energy transfer between FITC and RB, FITC was grafted onto the surface of core–shell silica colloidal particles with a shell thickness of 10–12 nm. The nanoprobe exhibited dual emission bands centered at 517 and 570 nm, under single wavelength excitation of 488 nm. RB encapsulated in silica was inert to pH change and only served as reference signals for providing built-in correction to avoid environmental effects. Moreover, FITC ( λ em = 517 nm) showed high selectivity toward H + against metal ions and amino acids, leading to fluorescence variation upon pH change. Consequently, variations of the two fluorescence intensities ( F green / F red ) resulted in a ratiometric pH fluorescent sensor. The specific nanoprobe showed good linearity with pH variation in the range of 6.0–7.8. It can be noted that the fluorescent silica probe demonstrated good water dispersibility, high stability and low cytotoxicity. Accordingly, imaging and biosensing of pH variation was successfully achieved in HeLa cells.